Strategi Komunikasi Pembelajaran dengan Pemanfaatan Media Teknologi Informasi Komunikasi Selama Pandemi Covid-19 - Melati, Ega Hawa Ari; Fauziah, Faradilla; Maharani, Sylvia Veronica Putri (PAKAR Pendidikan, 2023)
This study argues that during the Covid-19 pandemic, educational institutions began using online learning communication strategies by utilizing Information and Communication Technology (ICT) media. This communication strategy is used so that educational institutions can continue to provide learning rights to students while at the same time keeping students safe from the risk of being exposed to the Covid-19 pandemic. The formulation of the problem related to the research being conducted is how to use learning communication strategies by utilizing ICT media during the Covid-19 pandemic, as well as using the most media in the learning process. The purpose of this research is to find out how the learning communication strategy is by utilizing ICT media during the Covid-19 pandemic, as well as knowing the majority of ICT media used. The research uses qualitative methods with a library approach that focuses on the concepts of communication strategy, learning communication, and ICT. This study found the results that: Every educational institution has implemented an online learning communication strategy by utilizing ICT media. The most frequently used ICT media are google meet, zoom, WhatsApp Group, google drive, line, and PowerPoint. Where these media are used in teaching and learning activities, attendance, and group discussions, up to the assignment, the frequency of using ICT media is carried out every day during teaching and learning activities. However, in implementing online learning communication strategies, there are still some obstacles experienced by severe students, such as networks, devices, and student control. However, on the other hand, it is able to facilitate students to receive good learning during the pandemic.